EMPLOYEE ENGAGEMENT IN COMPANY’S CSR STRATEGY - Gulak-Lipka, Patrycja; Jagielski, Michał; Taciak, Patryk Jakub (Journal of Positive Management, 2020)
The aim of the paper is to analyze and investigate the level of employees’ participation in socially responsible activities in one of the automotive factories located in Toruń, Poland. The company conducts many socially responsible initiatives; however, it cannot realize its CSR programs without engagement of its employees. The company is medium-sized enterprise, that is why every CSR activity and program can be realized by many managers and workers. One of the main reasons of conducting the study is a desire of verification if employees participate in CSR programs before the research was conducted, as also to measure if they are ready to take a part in socially responsible programs in the future. In order to achieve the aim of the research, the following objectives have been set: (1) to present the main assumptions of the corporate social responsibility concept; (2) to describe company’s stakeholders and to show the potential benefits they can achieve thanks to CSR strategy; (3) to measure and analyze employees’ participation in CSR programs conducted in the company and to check their readiness to engage in socially responsible activities in the future. The findings and their presentation are achieved based on the questionnaire survey described in the paper.